Stellar populations in the Carina region : The Galactic plane at l = 291° - Molina Lera, José Alejo (2016)
Context. Previous studies of the Carina region have revealed its complexity and richness as well as a significant number of early-type stars. However, in many cases, these studies only concentrated on the central region (Trumpler 14/16) or were not homogeneous. This latter aspect, in particular, is crucial because very di erent ages and distances for key clusters have been claimed in recent years. Aims. The aim of this work is to study in detail an area of the Galactic plane in Carina, eastward η Carina.We analyze the properties of di erent stellar populations and focus on a sample of open clusters and their population of young stellar objects and highly reddened early stars. We also studied the stellar mass distribution in these clusters and the possible scenario of their formation. Finally, we outline the Galactic spiral structure in this direction. Methods. We obtained deep and homogeneous photometric data (UBVIKC) for six young open clusters: NGC 3752, Trumpler 18, NGC 3590, Hogg 10, 11, and 12, located in Carina at l ~ 291°, and their adjacent stellar fields, which we complemented with spectroscopic observations of a few selected targets. We also culled additional information from the literature, which includes stellar spectral classifications and near-infrared photometry from 2MASS.We finally developed a numerical code that allowed us to perform a homogeneous and systematic analysis of the data. Our results provide more reliable estimates of distances, color excesses, masses, and ages of the stellar populations in this direction. Results. We estimate the basic parameters of the studied clusters and find that they identify two overdensities of young stellar populations located at about 1.8 kpc and 2.8 kpc, with EB-V ~ 0.1-0.6. We find evidence of pre-main-sequence populations inside them, with an apparent coeval stellar formation in the most conspicuous clusters. We also discuss apparent age and distance gradients in the direction NW-SE. We study the mass distributions of the covered clusters and several others in the region (which we took form the literature). They consistently show a canonical IMF slope (the Salpeter one). We discover and characterise an abnormally reddened massive stellar population, scattered between 6.6 and 11 kpc. Spectroscopic observations of ten stars of this latter population show that all selected targets were massive OB stars. Their location is consistent with the position of the Carina-Sagittarius spiral arm.